FOSTERING GREEN ENTREPRENEURIAL INTENTIONS: THE ROLE OF EDUCATIONAL ENVIRONMENTS IN SHAPING STUDENT ENTREPRENEURIAL ASPIRATIONS - Safitri, Camelia; Mulyadi, Hari; Sutarni, Nani; Ramdhany, Muhamad Arief (UNIVERSITAS NEGERI SURABAYA, 2024)
This research empirically investigates the relationship between the entrepreneurial learning environment and green entrepreneurial intentions among undergraduate students in Indonesia. Through a cross-sectional survey involving 470 respondents from diverse academic backgrounds, the study reveals significant correlations between the physical and mental dimensions of the entrepreneurial learning environment and students' intentions toward green entrepreneurship. These dimensions encompass infrastructure, resources, and support systems, as well as attitudes, values, and perceptions cultivated within the learning environment. The findings underscore the pivotal role of fostering an educational atmosphere that nurtures innovation, creativity, and sustainability in shaping students' entrepreneurial aspirations, particularly toward green entrepreneurship. Furthermore, actionable recommendations are provided for university management, including integrating individuals with practical entrepreneurial experience into teaching, adapting entrepreneurship curriculum to incorporate principles of environmental sustainability, and empowering students through mentorship and practical experiences. Overall, this study contributes to the literature by highlighting the crucial role of the entrepreneurial learning environment in cultivating environmentally conscious entrepreneurs, not only in Indonesia but also in broader global contexts.